TorakochirurgiaThe use of silicone Y endoprosthesis in trachea bifurcation neoplastic stenoses treatment - Grochowski, Zbigniew; Olechnowicz, Henryk; Gil, Tomasz; Czajkowski, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Airway obstruction caused by malignant tumours is a difficult therapeutic problem. Aim: The target was to assess the efficacy of trachea bifurcation Y silicone prosthesis in inoperable bronchial tree neoplastic stenosis and to assess radio- and/or chemotherapy efficacy after the restoration of airway patency and stent implantation. Material and methods: 37 patients had a silicone Y tube implanted in the trachea and main bronchi. The patients’ clinical condition was examined before and after stent implantation; general condition was assessed on the Karnofsky scale; spirometry and gasometry were performed. Results: After trachea bifurcation prosthesis implantation an improvement of patients’ general condition was observed; the mean number of points on the Karnofsky scale increased from 37.3 to 66.5. Mean VC value increased from 1632 to 2208 ml; gas-exchange improved. Mean observation time was 171 days. Conclusion: The silicone Y stent implantation to trachea bifurcation in inoperable neoplasms causing respiratory tract stenosis immediately removes dyspnoea and brings about general improvement in condition. The possibility of combined treatment is essential.